2022
DOI: 10.1039/d1cy02089g
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved in situ DRIFTS study on NH3-SCR of NO on a CeO2/TiO2 catalyst

Abstract: Ce–Ti catalysts were considered as promising replacement for V–Ti based catalysts for selective catalytic reduction (SCR) of nitrogen oxides (NO and NO2) with NH3. In this work, CeO2/TiO2 catalyst was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Therefore, the results above provided direct evidence for the regeneration of the vanadyl species identified by our DFT calculations, where NO 2 oxidizes V 3+ to V 5+ , synchronized with the release of NO (F → G in Figures and ). In addition, the ammonium nitrate route has been proposed as a low-temperature FSCR mechanism. ,, But we demonstrated that the “ammonium nitrate route” is not the main pathway in our V 2 O 5 /TiO 2 catalytic system by NO 2 –SCR and NO 2 –SCR-TPD experiments (Figure ). N 2 O is the inevitable species for the decomposition of NH 4 NO 3 below 300 °C (Figure S18).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, the results above provided direct evidence for the regeneration of the vanadyl species identified by our DFT calculations, where NO 2 oxidizes V 3+ to V 5+ , synchronized with the release of NO (F → G in Figures and ). In addition, the ammonium nitrate route has been proposed as a low-temperature FSCR mechanism. ,, But we demonstrated that the “ammonium nitrate route” is not the main pathway in our V 2 O 5 /TiO 2 catalytic system by NO 2 –SCR and NO 2 –SCR-TPD experiments (Figure ). N 2 O is the inevitable species for the decomposition of NH 4 NO 3 below 300 °C (Figure S18).…”
Section: Resultsmentioning
confidence: 72%
“…In addition, the ammonium nitrate route has been proposed as a lowtemperature FSCR mechanism. 14,28,55 But we demonstrated that the "ammonium nitrate route" is not the main pathway in our V 2 O 5 /TiO 2 catalytic system by NO 2 −SCR and NO 2 − SCR-TPD experiments 7). N 2 O is the inevitable species for the decomposition of NH 4 NO 3 below 300 °C (Figure S18).…”
Section: mentioning
confidence: 73%
“…8(a). [53][54][55] Fig. 8(c) shows the in situ infrared spectrum of the CuCe/ VMT(M) catalyst for the co-adsorption of NO and CO.…”
Section: Reaction Mechanism Researchmentioning
confidence: 99%
“…On the other hand, TiO 2 has three main crystalline structures including rutile, anatase and brookite [19], where rutile and anatase are popularly used for photocatalysts and SCR catalysts [20][21][22]. Compositing CeO 2 /TiO 2 compound is an available method to improve the catalytic properties, and which has been studied as excellent photocatalysts [23][24][25] or SCR catalysts [26][27][28].…”
Section: Introductionmentioning
confidence: 99%